The Therapeutic Role of ADSC-EVs in Skin Regeneration - Wang, Yixi; Cheng, Lihui; Zhao, Hanxing; Li, Zhengyong; Chen, Junjie; Cen, Ying; Zhang, Zhenyu (Frontiers in Medicine, 2022)
Large skin defects caused by burns, unhealing chronic wounds, and trauma, are still an intractable problem for clinicians and researchers. Ideal skin regeneration includes several intricate and dynamic stages of wound repair and regeneration of skin physiological function. Adipose-derived stem cells (ADSCs), a type of mesenchymal stem cells (MSCs) with abundant resources and micro-invasive extraction protocols, have been reported to participate in each stage of promoting skin regeneration via paracrine effects. As essential products secreted by ADSCs, extracellular vesicles (EVs) derived from ADSCs (ADSC-EVs) inherit such therapeutic potential. However, ADSC-EVs showed much more clinical superiorities than parental cells. ADSC-EVs carry various mRNAs, non-coding RNAs, proteins, and lipids to regulate the activities of recipient cells and eventually accelerate skin regeneration. The beneficial role of ADSCs in wound repair has been widely accepted, while a deep comprehension of the mechanisms of ADSC-EVs in skin regeneration remains unclear. In this review, we provided a basic profile of ADSC-EVs. Moreover, we summarized the latest mechanisms of ADSC-EVs on skin regeneration from the aspects of inflammation, angiogenesis, cell proliferation, extracellular matrix (ECM) remodeling, autophagy, and oxidative stress. Hair follicle regeneration and skin barrier repair stimulated by ADSC-EVs were also reviewed. The challenges and prospects of ADSC-EVs-based therapies were discussed at the end of this review.